Antiviral and Antioxidant Activity of a Hydroalcoholic Extract from Humulus lupulus L. (24th July 2018) - Di Sotto, Antonella; Checconi, Paola; Celestino, Ignacio; Locatelli, Marcello; Carissimi, Stefania; De Angelis, Marta; Rossi, Valeria; Limongi, Dolores; Toniolo, Chiara; Martinoli, Lucia; Di Giacomo, Silvia; Palamara, Anna Teresa; et al.
Abstract : A hydroalcoholic extract from female inflorescences of Humulus lupulus L. (HOP extract) was evaluated for its anti-influenza activity. The ability of the extract to interfere with different phases of viral replication was assessed, as well as its effect on the intracellular redox state, being unbalanced versus the oxidative state in infected cells. The radical scavenging power, inhibition of lipoperoxidation, and ferric reducing activity were assayed as antioxidant mechanisms. A phytochemical characterization of the extract was also performed. We found that HOP extract significantly inhibited replication of various viral strains, at different time from infection. Viral replication was partly inhibited when virus was incubated with extract before infection, suggesting a direct effect on the virions. Since HOP extract was able to restore the reducing conditions of infected cells, by increasing glutathione content, its antiviral activity might be also due to an interference with redox-sensitive pathways required for viral replication. Accordingly, the extract exerted radical scavenging and reducing effects and inhibited lipoperoxidation and the tBOOH-induced cytotoxicity. At phytochemical analysis, different phenolics were identified, which altogether might contribute to HOP antiviral effect. In conclusion, our results highlighted anti-influenza and antioxidant properties of HOP extract, which encourage further in vivo studies to evaluate its possible application.